How Do Auditors Behave During Periods of Market Euphoria? The Case of Internet IPOs* - Leone, Andrew J.; Rice, Sarah; Weber, Joseph P.; Willenborg, Michael (Contemporary Accounting Research, 2013)
How do auditors behave during periods of market euphoria? To address this question, we study auditor going-concern opinions around the time of the wave of stressed Internet companies filing to go public on Nasdaq, a period many characterize as the ‘dot com bubble’. We focus on the day the auditor signs the opinion that appears in a stressed, Internet registrants’ IPO filing and document a sharp increase in the number of opinions with dates between January 1999 and April 2000. Contemporaneous with this jump in transaction volume, and for the duration of these 16-months, Big 5 firms were less likely to render going-concern opinions to their stressed, Internet IPO registrant clients. Upon conducting tests for determinants that could lead auditors to shift their decision criteria during this euphoric audit market, we find the presence of a going-concern opinion varies with variables that proxy for client reasons (financial distress, company age, venture backing, IPO cash burn) and for less auditor independence/skepticism (recent fees for clients without venture backing and a rush-to-market for clients with venture backing) by the Big 5 firms. These findings suggest a mixed conclusion regarding the Big 5's behavior; as the presence of a going-concern opinion varies inversely with variables that proxy for both client viability and auditor self interest. As for consequences to investors, our analysis of two, three and four-year post-IPO stock delisting provides some evidence of a decrease in the predictive content (early-warning value) of Big 5 opinions signed during the Internet IPO bubble.